Innovation Clusters: Advantages and Disadvantages - Mazur, Vladimir V.; Barmuta, Karine A.; Demin, Sergey S.; Tikhomirov, Evgeny A.; Bykovskiy, Maxsim A. (International Journal of Economics and Financial Issues, 2016)
The main direction of the current economic development is found in a transition of the most civilized countries to a new stage of creating an innovative society, i.e. building the economy based mainly on offering, spreading and using of knowledge. The specific functioning of innovation clusters allowing to create new technologies, implement deep technological modernization and innovative industry development based on personal or adopt technologies, as well as to train personnel for work in the conditions of the current industrial and technological formation, is characterized by the three components: the fundamental, practice-oriented science, innovative industry, and developing education. Along with that, nowadays there is a need to take firm measures not only to revive the innovative activity, but also to make a breakthrough in this area. Therefore, it is necessary to provide the state-of-the-art mechanisms to increase the innovative activity of domestic high-tech innovative economy based on the cluster approach, cluster initiatives. Keywords: innovation, cluster, disadvantages, creation, advantages, economy JEL Classifications: A11, A10, O30